Interest free economy promulgated by the Qur'an - Naik, Zakir, 1965-; Saba Islamic Media; Islamic Research Foundation ([Kuala Lumpur] : Saba Islamic Media)
A talk that discuss on economic and financial matters in context of Islam or Islamic financing, held in Bombay, India on Sunday, 19 May 1995
Title from title screen
Speaker: Dr. Zakir Abdul Karim Naik
Keywords: Interest (Islamic law); Finance -- Religious aspects -- Islam; Banks and banking -- Religious aspects -- Islam